Imitating Jesus: an inclusive approach to New Testament ethics - Burridge, Richard A. (Eerdmans, 2008)
Being 'biblical' : contexts and starting points -- Jesus of Nazareth : great moral teacher or friend of sinners -- Paul : follower or founder -- Mark : suffering for the kingdom